(untitled) (Research, Society and Development, 2023)
The aim of this study was to analyze the biological behavior and osteogenic potential of nanostructured hydroxyapatite microspheres substituted with strontium (nHASr). Therefore, twenty adult male Wistar rats were randomly distributed into two groups: GnHASr – critical bone defect filled with nHASr microspheres; e CG (control group) – critical bone defect without implantation of biomaterial; evaluated at the biological points of 30 and 60 days. The collected specimens were processed and stained with hematoxylin-eosin (HE) and Masson-Goldner trichrome (TG) and examined by light microscopy. Posteriorly, they were analyzed histomorphometrically to measure the percentage of neoformed osteoid matrix (%OM). In both groups studied, at all biological points, deposition of reparative osteoid matrix (OM) was observed near the bone edges; discrete chronic inflammatory response; connective tissue formation and neovascularization in the residual area of the defect. In the GnHASr, in the two evaluated periods, the deposition of OM was also noticed, both around and inside the microspheres. At 60 days, an area of 7.54% of OM deposition in relation to the total defect area was evidenced in the GnHASr, while in the CG this value was 6.80%. It is concluded that the nHASr microspheres evaluated were biocompatible, biodegradable, bioresorbable, bioactive and osteoconductive. In both groups, the formation of neomineralized tissue occurred in a limited way, which indicates that the concentration of metal used in the replacement did not favor greater osteogenic potential for the biomaterial. The evaluated biomaterial it’s adequate for use as a filling material.